Analisis Keseimbangan Dan Power Otot Lengan Terhadap Kemampuan Lempar Cakram - Ashari Efendi; Amrizal Amrizal; Seri Mughni Sulubara (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
of this research entitled "Analysis of Balance and Arm Muscle Power with Discus Throwing Ability in Class X Students of SMA Negeri 1 Bandar Bener Meriah Regency.". This study aims to determine the relationship between balance and arm muscle power and discus throwing ability in Class X students of SMA Negeri 1 Bandar, Bener Meriah Regency. . This research uses a quantitative approach with a type of correlation. The population in this study were all Class X students of SMA Negeri 1 Bandar, Bener Meriah Regency. For this research sample, the author determined the total sampling sample, that is, the total sample was 23 people. Data collection techniques are: (1) balance test using the modified bass test (2) arm muscle power test and (3) discus throwing ability test. The data analysis technique used is correlation. From the results of data analysis, research results were obtained, namely: (1) there was a positive and significant relationship between balance and discus throwing (r = 0.61), arm muscle power contributed 32.46% to discus throwing ability. (2) there is a positive and significant relationship between balance and discus throwing ability (r = 0.75), arm muscle power contributes 55.862% to discus throwing ability, and (3) there is a positive and significant relationship between balance and muscle power arm together with disc sheet ability (r = 0.78). Balance and arm muscle power contribute 63.84% to discus throwing ability together.